Optimasi Metode Kerja Line Packing pada Mesin Filling Multiline 6 di PT XYZ dengan Metode DMAIC - Nugroho, Irvan; Rahayu, Siti; Mukhlisin, Mukhlisin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Optimization of work methods is a key step to improving operational efficiency, particularly in the manufacturing industry which faces high cost pressures. This research was conducted at PT XYZ, a company specializing in processing cooking spices and sauces, located in the strategic industrial area of Jababeka, Cikarang. The study focused on the packing line of the filling machine ML6 with the aim of identifying, analyzing, and optimizing work methods using the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The results showed that implementing the DMAIC method successfully reduced idle time, balanced the workload among operators, and increased packing line productivity. These improvements led to annual cost savings of Rp244,674,216 and a workforce efficiency increase of 25%. Thus, the DMAIC approach has proven effective in addressing operational problems and significantly contributes to cost reduction as well as increased production process efficiency